Reductant-free synthesis of magnetoplasmonic iron oxide-gold nanoparticles. Issue 17 (1st December 2017) - Miola, Marta; Ferraris, Sara; Pirani, Federica; Multari, Cristina; Bertone, Elisa; Žužek Rožman, Kristina; Kostevšek, Nina; Verné, Enrica
Abstract: Stable suspensions of spherical 10–15 nm superparamagnetic iron oxide nanoparticles (SPIONs) have been synthetized by co-precipitation, stabilized with citric acid, surface functionalized with aminopropyltriethoxysilane (APTES) and finally decorated with ultra-small gold nanoparticles (GNPs) by in situ reduction of a soluble gold salt (HAuCl4 ), obtaining well dispersed SPIONs-GNPs colloids. The morphology, size and stability of the SPIONs-GNPs suspensions have been controlled by adjusting the molar ratio of the reagents (Fe/HAuCl4 and Fe/APTES). The synthesis route differs from that typically found in literature, using tunable chelating layer modifications (such as citric acid and –NH2 groups) of the magnetic core, depositing GNPs on the amine-functionalized iron oxide surface without the use of a specific reducing agent, and tuning the process pH and temperature. An explanation of how the different chemical species involved in the synthesis route could be responsible for the reducing action has been provided. The SPIONs-GNPs colloids have been characterized after each synthesis step by Transmission Electron Microscopy (TEM), Scanning Transmission Electron Microscopy (STEM), energy-dispersive X-ray spectroscopy (EDXS), Fourier transform infrared spectroscopy (FTIR), ζ Potential measurements, magnetic measurements with a vibrating-sample magnetometer (VSM) and UV–VIS spectroscopy. The SPIONs-GNPs colloids showed magnetoplasmonic behaviors since they maintained the plasmonic properties of GNPs and the superparamagnetic response of iron oxide NPs.